2021
DOI: 10.1097/md.0000000000024485
|View full text |Cite
|
Sign up to set email alerts
|

A strengthening the reporting of observational studies in epidemiology (STROBE)

Abstract: Paget disease is a complex disorder that can be identified in the breast (mammary Paget disease) or in other locations (extramammary Paget's disease) such as ano-genital skin (Paget disease of the vulva -PVD). This condition is associated with low mortality, but a late diagnosis and recurrence can negatively impact the prognosis. Therefore, the main objective of this study is to evaluate if the human epididymis protein 4 (HE4) and cancer antigen125 (CA125) can promote recognition of PVD in early stages and dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In case of persistence of positive margins, adjuvant therapy with GnRH analogues (e.g., triptorelin) is recommended until clinical negativity and for at least 6–9 months after surgery. The use of an aromatase inhibitor (letrozole) or a selective estrogen receptor modulator (SERM—e.g., tamoxifen, raloxifen) has been proposed as a second-line hormonal therapy in non-pregnant patients [ 10 , 11 , 12 , 38 ]. The role of radiotherapy is limited, and there is no evidence in the literature that adjuvant radiotherapy lowers the recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of persistence of positive margins, adjuvant therapy with GnRH analogues (e.g., triptorelin) is recommended until clinical negativity and for at least 6–9 months after surgery. The use of an aromatase inhibitor (letrozole) or a selective estrogen receptor modulator (SERM—e.g., tamoxifen, raloxifen) has been proposed as a second-line hormonal therapy in non-pregnant patients [ 10 , 11 , 12 , 38 ]. The role of radiotherapy is limited, and there is no evidence in the literature that adjuvant radiotherapy lowers the recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…In pregnant women, DAM typically presents as an indolent polypoidal mass, frequently with consistent dimensions, arising from the genitalia or perineum. Due to its appearance, DAM is often misdiagnosed as other more frequent conditions, such as a Bartholin’s cyst, lipoma, labial cyst, Gartner’s duct cyst, condyloma acuminata, vaginal prolapse, or an unspecified tumor [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The diagnosis is performed by the pathologist and not by the clinician, thanks to immunohistochemistry, which is essential to distinguish DAM from other benign stromal tumors of the lower genital tract.…”
Section: Introductionmentioning
confidence: 99%
“…This study has been reported using the Strengthening the Reporting of Observational Studies in Epidemiology cross-sectional checklist. 21 The preliminary arm recruited patients from community pharmacies in Southwest London whereby study procedures were conducted by community pharmacists.…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted as a multi-arm, non-interventional, cross-sectional study of patients with type 2 diabetes in England from August 2019 to May 2021. This study has been reported using the Strengthening the Reporting of Observational Studies in Epidemiology cross-sectional checklist 21. The preliminary arm recruited patients from community pharmacies in Southwest London whereby study procedures were conducted by community pharmacists.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue specimens of the tumor were obtained from patients who underwent surgery at our institution. Because of the rarity of this malignant cutaneous tumor [14], it is sometimes difficult for a diagnosis of extramammary Paget's disease to be made, especially as it is hard to distinguish the disease from the pagetoid phenomenon. To exclude a pagetoid phenomenon, perianal extramammary Paget's disease was evaluated via GCDFP15+ and CK20-to determine the correctness of the diagnosis of extramammary Paget's disease.…”
Section: Patient Populationmentioning
confidence: 99%